Antidepressants: Myths, facts and perspectives - Obradović Aleksandar Lj; Savić Miroslav M. (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
Antidepressants are one of the most widely used and criticized drug classes. Long-term effects leading to clinical efficacy of antidepressants in indications such as depression or anxiety disorders are poorly understood. The analysis of clinical trials suggests that, to a substantial degree, listening to antidepressants means hearing placebo. The precipitation of suicidal ideation is a possibility that needs to be considered when introducing antidepressants, especially in young patients. The discontinuation symptoms following cessation of treatment emerge frequently, and essentially are manifestations of withdrawal. Many, if not most, patients require multiple modifications in treatment in order to reach remission and avoid relapse or recurrence. However, these drugs are needed in clinical practice, and it is of paramount importance to precisely tailor treatment with antidepressants and adjunctive drugs to achieve optimal efficacy with minimal adverse effects. There are also hopes that novel drugs with rapid ketamine-like antidepressant actions may be introduced in the near future, thus solving the issue of acute management of severe depressions.